Impactos ambientales por la composición de fluidos utilizados en la estimulación hidráulica eficiente en yacimientos no convencionales desde un contexto internacional (2016)
The general objective of this monograph was to evaluate the composition of the fluid for hydraulic stimulation in unconventional reservoirs. To achieve its purpose, the state of the art used as a reference to support the information was updated, mainly for the United States, the country with the largest number of wells where hydraulic fracturing has been carried out. Then, the information was organized and the writing of the chapters began, which in this case were divided into three, among which are: the composition of the fracturing fluid taking into account the base fluid and the possible constituent additives ; Subsequently, different case studies obtained in the industry in which the operation had been carried out were analyzed, taking into account the water used and the ratio of the additives used; and, finally, the environmental impacts that the operation and the fluid generate in the nearby towns where the project is executed were developed.